The Influence of Service Features, Benefits, and Security Perceptions on Public Interest in Using the Dana Digital Wallet in The City of Semarang - Desvita Fitriana; R. Gunawan Setianegara; Aris Sunindyo Arif Mursito (Politeknik Negeri Semarang, 2025)
This study aims to analyze and obtain empirical evidence regarding the influence of service features, perceived benefits, and security perceptions on the use of the DANA digital wallet in Semarang City. The population in this study consists of residents living in Semarang City. The sampling technique used is purposive sampling with a total of 100 respondents. The data used in this study are primary data obtained through the distribution of questionnaires. The analytical model employed is Multiple Linear Regression Analysis. The data analysis techniques include the F-test, Coefficient of Determination (R²), and t-test. The results of the study indicate that the variables of service features, perceived benefits, and security perceptions simultaneously have a significant effect on the interest of the community in using the DANA digital wallet in Semarang City. Each of the variables service features, perceived benefits, and security perceptions also has a significant partial effect on the community's interest in using the DANA digital wallet in Semarang City.